(untitled) - Lind, Douglas A. (Boston, 2004)
STATISTICAL TECHNIQUES IN BUSINESS AND ECONOMICS, 12/e is a market best seller due to the comprehensive coverage of statistical tools and methods delivered in a student friendly, step-by-step format. The text is non-threatening and presents concepts clearly and succinctly with a conversational writing style. All statistical concepts are illustrated with solved applied examples immediately upon introduction. Modern computing tools and applications are introduced, though the text maintains a focus on presenting statistitcs concepts as applied in business as opposed to technology or programming methods. The twelfth edition continues as a ‘students’ text with increased emphasis on interpretation of data and results.
Keywords: Social sciences,Economics,Commercial statistics; Statistical methods,Statistical methods